Developing biodiversity-based solutions for sustainable food systems through transdisciplinary Sustainable Development Goals Labs (SDG-Labs) - Jarzebski, Marcin Pawel; Su, Jie; Abrahamyan, Armine; Lee, Jason; Kawasaki, Jintana; Chen, Bixia; Andriatsitohaina, R. Ntsiva N.; Ocen, Ismael; Sioen, Giles Bruno; Lambino, Ria; Saito, Osamu; Elmqvist, Thomas; et al. (Frontiers in Sustainable Food Systems, 2023)
Although biodiversity is a central component of food systems, conventional food systems have become one of the major drivers of biodiversity loss globally. There is an increasing need to transform food systems to provide sufficient and nutritious food, but with minimal negative impacts on the environment and society. One of the possible avenues to enable the sustainable transformation of food systems might be through the development of locally appropriate biodiversity-based solutions. In this paper we report the insights and lessons learned during the design and implementation of transdisciplinary projects that employed the concept of Sustainable Development Goals labs (SDG-Labs) to create biodiversity-based solutions to transform food systems. The six SDG-Labs outlined in this paper were implemented in Armenia, China, Japan, Madagascar, Thailand, and Uganda. Collectively they developed very diverse biodiversity-based solutions that used different components of biodiversity, ranging from novel cultivation systems with endangered plants, to gardens using tree species for wind breaks, or novel tea-forestry production systems. Beyond their ability to leverage different components of biodiversity to transform local food systems (also conserving biodiversity in the process), all solutions had multiple co-benefits such as climate change adaptation/mitigation and livelihoods generation, among other sustainability domains. Through a Strengths-Weaknesses-Opportunities-Threats (SWOT) analysis we synthesized the experiences gained during the design and implementation of all six SDG-Labs. The findings suggest the great promise of these transdisciplinary approaches for developing solutions at the biodiversity-food-climate nexus. However, this synthesis paper also points to the multiple context-specific challenges that should be overcomed to maximize the potential of SDG-Labs to both enable the sustainable transformation of (local) food systems and/or be scaled up effectively.